In vitro biophysical, microspectroscopic and cytotoxic evaluation of metastatic and non-metastatic cancer cells in responses to anti-cancer drug. Issue 24 (3rd November 2015) - Li, Qifei; Xiao, Lifu; Harihar, Sitaram; Welch, Danny R.; Vargis, Elizabeth; Zhou, Anhong
Abstract : Breast cancer cells with or without BRMS1 in response to doxorubicin (DOX). Abstract : The Breast Cancer Metastasis Suppressor 1 (BRMS1) is a nucleo-cytoplasmic protein that suppresses cancer metastasis without affecting the growth of the primary tumor. Previous work has shown that it decreases the expression of protein mediators involved in chemoresistance. This study measured the biomechanical and biochemical changes in BRMS1 expression and the responses of BRMS1 to drug treatments on cancer cells in vitro . The results show that BRMS1 expression affects biomechanical properties by decreasing the Young's modulus and adhesion force of breast cancer cells after doxorubicin (DOX) exposure. Raman spectral bands corresponding to DNA/RNA, lipids and proteins were similar for all cells after DOX treatment. The expression of cytokines were similar for cancer cells after DOX exposure, although BRMS1 expression had different effects on the secretion of cytokines for breast cancer cells. The absence of significant changes on apoptosis, reactive oxygen species (ROS) expression and cell viability after BRMS1 expression shows that BRMS1 has little effect on cellular chemoresistance. Analyzing cancer protein expression is critical in evaluating therapeutics. Our study may provide evidence of the benefit of metastatic suppressor expression before chemotherapy.